2019
DOI: 10.1186/s12891-019-2718-6
|View full text |Cite
|
Sign up to set email alerts
|

Plantar heel pain in middle-aged and older adults: population prevalence, associations with health status and lifestyle factors, and frequency of healthcare use

Abstract: Background The objectives of this study were to estimate the population prevalence and distribution of plantar heel pain in mid-to-older age groups, examine associations with selected health status and lifestyle factors, and report the frequency of healthcare use. Methods Adults aged ≥50 years registered with four general practices were mailed a health survey ( n = 5109 responders). Plantar heel pain in the last month was defined by self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 34 publications
2
61
1
1
Order By: Relevance
“…Plantar heel pain (PHP) is common in the community with an estimated prevalence between 3.6 and 9.6% [1][2][3][4], although there is a paucity of high-quality prevalence studies. PHP has a negative impact on healthrelated quality of life and is frequently associated with significant disability due to pain, and psychological distress [4][5][6][7]. The condition can be long-standing [8] and one study found that 1 in 5 patients took several days of sick leave due to their heel pain [9].…”
Section: Introductionmentioning
confidence: 99%
“…Plantar heel pain (PHP) is common in the community with an estimated prevalence between 3.6 and 9.6% [1][2][3][4], although there is a paucity of high-quality prevalence studies. PHP has a negative impact on healthrelated quality of life and is frequently associated with significant disability due to pain, and psychological distress [4][5][6][7]. The condition can be long-standing [8] and one study found that 1 in 5 patients took several days of sick leave due to their heel pain [9].…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, it has been found that women who wear high-heeled footwear do not have the effect of plantar fasciitis (Thomas et al, 2019). This is because the higher elevation serves as off load (Yu et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
“…In previous research articles, it has been said that older people at the age of above 65 years are getting more affected (Dunn, 2004). This condition called plantar fasciitis can be caused due to increased body mass index (Irving et al, 2007), anxiety and stress (Cotchett et al, 2014) and also due to prolonged standing related to the occupation (Thomas et al, 2019). In some previous literatures, plantar fasciitis is also termed as she will spur syndrome, runners share and calcaneal periostitis (Roxas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Plantar heel pain typically affects highly physically active people, such as running athletes, but is also common in middle-aged (40 to 60 years) women with high body mass index (BMI). [3][4][5][6] The incidence of plantar heel pain in Dutch general practice is approximately 3.8 per 1000 patientyears. 7 The clinical course of plantar heel pain is considered favourable with remission after 12 to 24 months in 60% to 80% of patients.…”
Section: Introductionmentioning
confidence: 99%